2015
DOI: 10.1128/aem.03082-14
|View full text |Cite
|
Sign up to set email alerts
|

Organic Substances Interfere with Reverse Transcription-Quantitative PCR-Based Virus Detection in Water Samples

Abstract: bReverse transcription (RT)-PCR-based virus detection from water samples is occasionally hampered by organic substances that are coconcentrated during virus concentration procedures. To characterize these organic substances, samples containing commercially available humic acid, which is known to inhibit RT-PCR, and river water samples were subjected to adsorption-elution-based virus concentration using an electronegative membrane. In this study, the samples before, during, and after the concentration were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Organic substances are known to interfere with this step in the processing of environmental samples and thereby can reduce the precision and robustness of the detection in direct comparison to DNA viruses like HAdV [58] which could explain the shift in the detection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Organic substances are known to interfere with this step in the processing of environmental samples and thereby can reduce the precision and robustness of the detection in direct comparison to DNA viruses like HAdV [58] which could explain the shift in the detection rates.…”
Section: Discussionmentioning
confidence: 99%
“…With higher MW, humic acid tends to be more aromatic and absorptive [24,25]. The same humic acid products (Ald, Wa, and IH) were studied and found that the peak MW of Ald and Wa were between 10 and 100 kDa while this value of IH was only around 1.0 kDa [17]. Therefore, it might result in the higher recovery of Ald, Wa, and Na than that of IH in the 1st concentration step.…”
Section: Co-concentration Properties Of Humic Acids During the Virus mentioning
confidence: 99%
“…Previous studies reported that humic acid can be co-concentrated by membrane filtration due to its adsorptive properties [17,23], which depend on the MW [24]. With higher MW, humic acid tends to be more aromatic and absorptive [24,25].…”
Section: Co-concentration Properties Of Humic Acids During the Virus mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the RT reactions for standard curves constructed using Sensiscript and Omniscript produced reliable Cts at target concentrations as low as 10 3 copies/µl, similar to that observed for SSIV and SSIII (except for Sensi-RH: lower limit at 10 4 copies/µl). This indicates that the lower performances observed for Sensiscript and Omniscript in the environmental spike experiment could be due to inhibition of the enzymes from co-extracted components in environmental RNA(Hata et al, 2015) and/or the presence of background RNA. The later explanation contrasts with the results obtained by Levesque-Sergerie and co-workers(Levesque-Sergerie et al, 2007) who observed a general increase in the recovered copies of a spike (i.e.…”
mentioning
confidence: 99%